An Update on the Role of the Actin Cytoskeleton in Plasmodesmata: A Focus on Formins - Diao, Min; Huang, Shanjin (Frontiers in Plant Science, 2021)
Cell-to-cell communication in plants is mediated by plasmodesmata (PD) whose permeability is tightly regulated during plant growth and development. The actin cytoskeleton has been implicated in regulating the permeability of PD, but the underlying mechanism remains largely unknown. Recent characterization of PD-localized formin proteins has shed light on the role and mechanism of action of actin in regulating PD-mediated intercellular trafficking. In this mini-review article, we will describe the progress in this area.